3D Simulation of the Melting During an Electro-Slag Remelting Process - A. Kharicha; A. Ludwig; M. Wu (The Minerals, Metals and Materials Society, 2011)
"The droplet formation during melting of a 400 mm diameter electrode is simulated with a multiphase-MHD approach. The computational model includes a layer of slag and a layer of liquid steel. A VOF approach is used for the interface tracking and a potential formulation is used for the electric and the magnetic field. The Lorentz force and the Joule heating are recalculated at each time step in function of the phase distribution. The first results provided by this model are presented.IntroductionThe Electro-Slag-Remelting (ESR) process is an advanced technology for the production of components of e.g. high quality steels [ 1-9]. An alternating current (Figure 1) is passed from a conventionally melted and cast solid electrode through a layer of molten slag to the baseplate. Because of the electrical resistivity of the slag, Joule heating is generated and the slag transfers this energy to ingot and mould surfaces and to the melting electrode tip. The molten metal produced in the form of droplets passes through the slag and feeds a liquid pool from where directional solidification takes place. The slag and the ingot are contained in a water cooled copper mould. As also the baseplate is water cooled, a heat flow regime is imposed that gives controlled solidification, and this results in improved structure characteristics of ESR ingots.This process involves two liquids, a liquid metal and a liquid slag. Each liquid is subject to a phase change due to melting and/or solidification. From a fluid dynamic point of view, the ESR process is clearly a multiphase process, with free interfaces (slag/pool, gas/slag), and with a mixed area (slag and falling steel droplets) [ 10-15].Physically, the development of the heat and mass transfer at the slag/droplet interface is important for the final ingot quality, composition and cleanliness. Visual observations of the droplet formation just under the electrode being melted is almost impossible. Due to the presence of high temperatures, opacity of the materials, and the presence of the mould it is not possible to directly observe the behaviour the slag/pool interface. Although usually assumed flat [1-9], a previous work [10] using a Volume of fluid (VOF) model has shown that the interface shape between a layer of slag and steel layer in a cylindrical cavity is highly coupled with the distribution of the electric current. A full scale simulation of the ESR process using a VOF model has shown that the shape of the pool interface is likely to be non flat."